It's Not the Size of the Data -- It's How You Use It : Smarter Marketing with Analytics and Dashboards. - Pauwels, Koen (AMACOM, 2014)
Brand tracking, CRM programs, trade shows, online behavior tracking, satisfaction studies ... mounds of marketing metrics are generated across touchpoints and channels. For marketers drowning in data, dashboard analytics bring order to sprawling numbers, and accurate answers to questions about what's working and what's not. These web-based tools gather, synthesize, and visually display essential data in real time, directly connecting marketing with performance. With its rigorous methodology, wealth of case studies, and step-by-step instructions, this substantial guidebook explains how to set up.